Bridging heritage and modernity: A comparative study of traditional Chinese and western flower-and-bird paintings - Gao Xue; Musnin Bin Misdih (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2025)
The research paper investigates the minute intricacies of the correlation between cultural philosophies and aesthetic traditions by conducting a comparative analysis of the flower-and-bird motifs between traditional Chinese and Western paintings. The research uses the theory of Erwin Panofsky's Iconography and Iconology framework to examine the painting techniques which include brushstrokes, color, and composition that identify the way these elements reflect the broader cultural attitude towards nature. Chinese paintings, especially the ones relating to the Chang ’an School are known to be rooted in the Daoist and Confucian philosophies. This emphasizes harmony, interconnectedness, and balance. On the contrary, Western artworks of the same motif by artists such as Vincent van Gogh and Claude Monet focus on emotional depth through individual perspective and resonance. The paper conducts qualitative research through the incorporation of primary research data from the various artworks from both Chinese and Western artists as well as secondary data from existing academic literature which helped to analyses the symbolic and visual details. The primary findings of the research show that Chinese art is more focused on universal moral philosophies that use symbolic motifs whereas the Western approach priorities personal expression and highlights the transience of natural beauty. The paper concludes with a final recommendation for future research into the influence of globalization and digital technology on the traditional artistic forms and techniques which foster hybrid styles and create connectivity between the East and the West.